Perancangan Sistem Informasi Point of Sale Pada UD.Harapan Menggunakan Metode FIFO (First In First Out) - Yudha Adyatma Syifa; Agung Purwanto (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
Information systems are created with the aim to facilitate its users, business processes that were originally done manually with the information system then all business processes performed can be computerized properly. UD.Harapan is a business engaged in retail trade that has several problems in the business process they run, some of the problems faced are recording data on goods that take a long time, manual purchase and sale transactions so long to complete each transaction, and the most important is the recording of customer data starting from the balance stored and used is still recorded manually in a notebook. To support existing business processes in UD.Expectations are sales, purchases, recording stock, recording customer data, recording cash in and out, as well as reports needed a system to support all existing business processes. The purpose of this study is to create an information system to support all business processes in UD.Hope. In the manufacture of information systems used FIFO method (First In First out) to assist the recording of goods data. Making information systems using FIFO method and utilizing UML as a model of the design to be made has been able to be implemented in UD.Expectations and run as they need, this system has been tested using blackbox testing so that all existing features are successfully run by users as expected results.